KUALITAS PELAYANAN POLI KLINIK RAWAT JALAN PADA RUMAH SAKIT UMUM DAERAH CARUBAN KABUPATEN MADIUN PROVINSI JAWA TIMUR - Wuryani, Siti (JI@P, 2024)
Today health problems have become a basic need for society. Everyone wants health because health is considered very valuable and expensive. The hospital is one of the health facilities to provide health referral services to the community and has a very important role in accelerating the improvement of public health status. The problem found is the importance of the quality of outpatient polyclinic services at the Caruban Regional General Hospital, Madiun Regency, East Java Province. This study aims to analyze and describe the quality of outpatient polyclinic services at the Caruban Regional Hospital, Madiun Regency, East Java Province. The research uses the theory of 5 dimensions of service quality (SERVQUAL) according to Zeithaml et al (1990) in hardiyansyah (2011: 46-47) which consists of Tangible dimensions (Physical Evidence), Reliability (Reliability), Responsiveness (Responsiveness), Assurance (Assurance) , and Empathy (Empathy). The research sample was taken from patients who had received 2 (two) services at the outpatient polyclinic at the Caruban Regional General Hospital. The research methodology used a cross-sectional survey study which was carried out for approximately one month. Data was collected through a questionnaire that focused on various aspects of service, including speed of service, ease of access, quality of communication with medical personnel, available facilities. The results of this study indicate that the quality of outpatient services at the Caruban Regional General Hospital, Madiun Regency, is in the Good category with a total score of 754.67 or 3.85. The tangible dimension shows the Good category with a total score of 726.83 or 3.70. The Reliability dimension shows the Good category with a total score of 744.12 or 3.79. The Responsiveness dimension shows the Good category with a score of 773.63 or 3.77. The Assurance dimension shows the Good category or 3.94. Meanwhile, the Empathy dimension shows the Very Good category with a total score of 785.33 or 4.00. Keywords: Tangible dimension, reliability dimension, responsiveness dimension, assurance dimension and empathy dimension